Política de formação de professores nos institutos federais e a licenciatura em matemática do IFRS-Câmpus Bento Gonçalves - Bavaresco, Delair (Universidade do Vale do Rio dos Sinos, 2014)
This thesis aims to problematize Mathematics teacher education in teaching courses offered by Federal Institutes of Education, Science and Technology (IFs) with a specific focus on IFRS-Campus Bento Gonçalves (RS). This problematization comprehends the discussion about the conditions of possibility for the emergence of IFs with a determined number of vacancies for teaching courses in Mathematics and Sciences; the analysis of institutional actions related to the IFRS campus in Bento Gonçalves and associated with the implantation of the Mathematics teaching course; the examination of students utterances about their education and professional perspectives; and the configuration of both convergences and displacements between the purposes of the public policy of teacher education in IFs and the students‟ professional perspectives. Your main argument is expressed by the following statement: The teacher education policy in IFs has been ineffective regarding to Mathematics teaching course from IFRS campus Bento Gonçalves. The students have not shown interest in Elementary School teaching as a professional option, thus diverting from the goals intended for the course. The research material consists of official documents published by the Ministry of Education, particularly those related to SETEC; documents issued by the IFRS Bento Gonçalves campus; data from IBGE and other official databases; interviews with two managers and two professors from the institution; and interviews with 11 students from the first group that were about to finish their undergraduate course in Mathematics in IFRS-BG. The theoretical contributions that have supported this investigation are those linked to Michel Foucault‟s studies, particularly the notion of governmentality. The investigation has shown that: a) IFs emerged and had their institutional configuration defined in a scenario of educational reforms triggered by LDB in 1996, associated with social and economic changes in the country from the 1990s, which required labor qualification, development of science and technology, and teacher education with an emphasis on Sciences and Mathematics; b) IFRS campus in Bento Gonçalves started teacher education in alignment with the purposes of the creation of IFs, despite the discontinuity posed by the teaching courses in the institutional trajectory in technical professional education. Mathematics was chosen due to both the imposition of short deadlines for its implementation and institutional structure limitations; c) the Mathematics students do not regard Elementary School teaching as the main target of their education, and their professional perspectives include keeping their current jobs even though their activities are not related to education; and d) The students strategies for a superior formation in Mathematics teaching course of IFRS – BG present divergence related to the proposes of policy IFs teacher formation, since their interests and professional perspectives, with rare exceptions, do not include the teaching career on Basic Education.
Keywords: Instituto Federal; Formação de professores; Governamentalidade; Política educacional; Perspectiva profissional; Federal Institution; Teacher education; Governmentality; Educational policy; Professional perspective; ACCNPQ::Ciências Humanas::Educação